Peran Media dalam Proses Pembelajaran - doni, La Doni; Daud, La Ode Rahman (Universitas Muslim Buton, 2024)
Abstract The role of media in the learning process is an activity carried out by two parties, namely the teacher as facilitator and students as learning intermediaries to convey cognitive, affective and psychomotor messages. The method used in the research is the library method. This research studies and examines various kinds of literature regarding references. Be it in the form of books, articles, journals, and other information related to the discussion in this journal. Media is anything that can convey messages through various channels, such as stimulating someone's thoughts, feelings and desires so that it can encourage the creation of effectiveness in adding new information to someone. In terms of helping students or students find it easy to obtain information in their learning, there are many factors that cause the learning process to be successful if teachers can utilize media as a tool to carry out teaching optimally. Teachers are responsible for the success of learning activities. Therefore, along with advances in science and technology, teachers are required to keep up with the times. Although many teachers do not use learning media for the success of the teaching and learning process. Keywords : Role of Media, Process, Learning